2019
DOI: 10.7717/peerj.7025
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of plasma messenger RNA as novel biomarker for gastric cancer identified through bioinformatics analysis and clinical validation

Abstract: Background Gastric cancer (GC) is the third leading cause of cancer-related death worldwide, partially due to the lack of effective screening strategies. Thus, there is a stringent need for non-invasive biomarkers to improve patient diagnostic efficiency in GC. Methods This study initially filtered messenger RNAs (mRNAs) as prospective biomarkers through bioinformatics analysis. Clinical validation was conducted using circulating mRNA in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Several studies have reported that MMP-9 can induce invasiveness in the endometrial tissue, leading to the degradation of ECM, invading other locations, and creating ectopic endometriosis lesions (30,31). There are pieces of evidence suggesting that the MMP-9 gene is significantly overexpressed in the endometriosis tissue, which can be expected according to its role in endometriosis pathogenesis (13,27). The elevation of MMP-9 mRNA in the plasma of endometriosis patients, observed in this study, was consistent with the results of previous investigations on the expression MMP-9 in the endometriosis tissue, suggesting its potential as a non-invasive diagnostic biomarker for endometriosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several studies have reported that MMP-9 can induce invasiveness in the endometrial tissue, leading to the degradation of ECM, invading other locations, and creating ectopic endometriosis lesions (30,31). There are pieces of evidence suggesting that the MMP-9 gene is significantly overexpressed in the endometriosis tissue, which can be expected according to its role in endometriosis pathogenesis (13,27). The elevation of MMP-9 mRNA in the plasma of endometriosis patients, observed in this study, was consistent with the results of previous investigations on the expression MMP-9 in the endometriosis tissue, suggesting its potential as a non-invasive diagnostic biomarker for endometriosis.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that various kinds of RNAs, including mRNAs and non-coding RNAs, can be extracted and detected in body fluids such as plasma and serum (24,25). Indeed, several investigations have shown that cell-free mRNAs in plasma can be promising non-invasive diagnostic tools for cancer (26,27). Hence, in this study, the plasma levels of MMP-9 and VEGF-A mR-NAs, as the genes relevant to endometriosis pathogenesis, were evaluated by RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al analyzed the GEO database and showed that SERPINH1 was one of the five hub genes in GC [28]. Cao et al analyzed plasma mRNA profiles of 56 GC patients and 14 healthy individuals in the Oncomine database and demonstrated high SERPINH1 mRNA levels in the GC samples [29]. In this study, we analyzed SERPINH1 mRNA expression in 888 GC and 318 normal gastric mucosal tissues from three public databases (Oncomine, TCGA, and GEO).…”
Section: Discussionmentioning
confidence: 97%
“…Another study reported that the combination of lncRNA H19, MEG3, and miRNA miR-675-5p improved the diagnostic efficiency compared with using each alone [27]. Although previous studies showed that most biomarkers of GC are associated with cancer differentiation [14,17,29,30], and some RNAs in this study including CEBPA-AS1, IHNBA-AS1, and AK001058 exhibited increasing trends with tumour progression, the expressions of these RNAs were not associated with GC differentiation in heathy participants which should be closed to the high differentiation in patients with GC. Our study results suggest the need to consider healthy controls when assessing the relationship between expressions of biomarkers and cancer differentiation.…”
Section: Discussionmentioning
confidence: 99%